Applicability of intensive care in children with speech sound disorders: a systematic review (Research, Society and Development, 2020)
Objective: To characterize the methodology of intensive intervention in cases of Speech Disorders (DSF). Methodology: The search for scientific articles was conducted by two independent researchers in the Medline (Pubmed) databases, LILACS, SciELO, Cochrane Library and Scopus. The systematic review was conducted according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Results: After reading the articles in full, identification data and methods were extracted from the articles for further analysis. Intensive care for children with DSF has been shown to vary in terms of the intervention methodology, both in cases of phonological disorders and apraxia of speech in childhood. Conclusion: Studies are suggested comparing high-intensity versus low-intensity therapy in different DSF conditions, specifying the intensive intervention methodology, such as frequency and frequency dosing.